A Comprehensive Approach Combining Regulatory Procedures and Accident Data Analysis for Road Safety Management Based on the European Directive 2019/1936/EC - Rosolino Vaiana; Giusi Perri; Teresa Iuele; Vincenzo Gallelli (Safety, 2021)
The European Union policy for road safety management is based on the European Directive 2019/1936/EC. Among the safety management procedures and strategies, road safety inspections (RSI) are an effective tool for preventing accident risk and reducing crash frequency and severity for existing road networks. The European Transport Safety Council encourages the extension of these measures to the main urban and rural roads by the 5th Road Safety Action Programme. In light of the above, in this study, a safety performance evaluation through the RSI approach is carried out for a high-risk rural road in Southern Italy in order to identify all the road infrastructure-related features with poor safety conditions. Afterwards, the relationship between infrastructure deficiencies and the frequency and severity of accidents is investigated; a significant relationship between accident density/total number of injured people and road markings gap is found. Furthermore, the results confirm that a high density of driveways strongly impacts crash frequency. The analysis of the contribution of multiple infrastructure-related variables on the crash occurrences is proposed by the identification of several mathematical models. A second-order AIC (Akaike’s information criterion) approach is carried out to compare the five fitted models investigated. Finally, a prediction calibrated model is proposed.